Buttermilk as milk powder and whey substitute in compound milk chocolate: Comparative study and optimisation - Rasouli Pirouzian, Haniyeh; Alakas, Elif; Cayir, Merve; Yakisik, Elif; Toker, Omer Said; Kaya, Sevin; Tanyeri, Ozan (WILEY, 2021)
The aim of this study was to investigate the optimal concentration of milk, whey and buttermilk powder by using mixture design for the formulation of compound milk chocolate. The influence of buttermilk as a milk and whey substitute on the main physicochemical parameters of compound milk chocolate was investigated. The optimisation of the variables indicated that using 35.660% milk powder, 27.957% whey powder and 36.383% buttermilk produced the optimum milk chocolate with the highest desirability without undesirable changes in the quality properties. Chocolates containing equal amounts of buttermilk and milk powder and also equal amounts of whey powder and buttermilk powder demonstrated high consumer acceptability.
Keywords: Compound chocolate; Milk powder; Buttermilk; Mixture design; Optimisation; FAT; Food Science & Technology